Splenectomy and its relation to non-transfusion-transmitted infection in thalassemic patients - Mururul Aisyi; Alan Roland Tumbelaka; Bulan Ginting Munthe; Bambang Madiyono (Paediatrica Indonesiana, 2006)
Background Splenectomy has been associated with an increasedsusceptibility to infection. Overwhelming postspelenectomy infec-tion (OPSI) can lead to high mortality. Decreased IgM and tuftsinconcentration on splenectomized patients seems to play a role ininfection’s susceptibility. Many studies have been performed todetermine the risk factors of infection in thalassemic patients.Objective To find out morbidity patterns and risk factors for pre-dicting the likelihood of infection in splenectomized thalassemicpatients.Methods A retrospective cross sectional study was conducted onconfirmed thalassemic children who came to Department of ChildHealth, Cipto Mangunkusumo Hospital within the period of 1973-2003. Splenectomized patients were categorized as cases groupand non-splenectomized patients as control group. Risk factors fordevelopment of common cold and diarrhea were analyzed usingchi-square test with level of significance <0.05.Results A total of 300 thalassemic patients, 100 of them were sple-nectomized, were enrolled in this study. The 15-year-age group orabove is the most common group underwent splenectomy (35%).Common cold is the most common mild infection in both splenec-tomized group (75%) and non-splenectomized (71%). A significantassociation was found between the risk of infection and splenec-tomy in thalassemic patients (OR=3.8;CI=2.2;6.62; P=0.000). As-sociation between time after splenectomy and frequency of com-mon cold in thalassemia was significant (OR=2.85;CI=1.16;7.14;P=0.011). Severe infection and acute diarrhea were considerednot significantly different between the two groups.Conclusion Splenectomy in thalassemia can increase the sus-ceptibility of non-transfusion-transmitted mild infection. Furtherstudy is needed to elaborate this finding